Determinants of Preventive Behavior towards the Spread of Covid-19 among Ships that Docked at Boombaru Port, Palembang - Fahmi Rizal; Novrikasari Novrikasari; Nugi Nurdin (Poltekkes Kemenkes Palu, 2023)
Boombaru Port in Palembang is a meeting point for the activities of ships, goods and people with the potential to become a means of the spread of Covid-19. Current efforts to prevent the spread of Covid-19 have not been fully implemented optimally. This study aims to analyse the determinants of preventive behavior towards the spread of Covid-19. This was a quantitative study using descriptive analytical method with a cross sectional approach. The study population was all crew members of ships that docked at Boombaru Port, Palembang with a total sample of 114 respondents who were selected accidentally. Data were analyzed using chi-square test and multiple logistic regression. The results showed several variables with a significant correlation, namely Captain support (P-value=0.0001) and availability of facilities (P-value=0.0001). Meanwhile, there were no significant correlations between age (P-value=1), education (P-value=0.612), type of ship (P-value=0.748), knowledge (P-value=1), attitude (P-value=0.279) with the preventive behavior towards the spread of Covid-19. In conclusion, the most dominant variable related to Covid-19 preventive behavior was captain support (PR=35.605). Poor Captain support had a 35.606 times greater risk to create bad preventive behavior towards the spread of Covid-19 compared to good Captain support.